Continuous Improvements to Calibrated, Enhanced-Resolution Brightness Temperatures (CETBs) for Near Real-Time Cryospheric Applications ... - Hardman, M. A.; Brodzik, M. J.; Long, D. G.; Meier, W. N.; Miller, J. Z.; Ramage, J. M.; Stewart, J. S. (Zenodo, 2022)
Since the release of the Calibrated, Enhanced-Resolution Brightness Temperature (CETB) Earth System Data Record (ESDR) in 2017, the cryospheric research community has been using this long-term data record to update derived geophysical parameters. This global, gridded data set is a fundamental tool in studying surprisingly rapid cryospheric change in the satellite era. The CETBs make use of an innovative computational algorithm, the radiometer version of Scatterometer Image Reconstruction (rSIR), to improve spatial resolution of the products to 3 km (30-60% over conventional gridding techniques). With data beginning in 1978, CETBs provide a 40+ year record of Earth’s passive microwave emissions from multiple, often overlapping, polar orbiting sensors. Recent sensor additions to CETBs include Soil Moisture Active Passive (SMAP) radiometer and Advanced Microwave Scanning Radiometer 2 (AMSR2). We now produce daily CETBs in near real- time for operational sensors (3 SSMIS, SMAP and AMSR2). Developed with FAIR ...